2007
DOI: 10.1016/j.pain.2006.09.031
|View full text |Cite
|
Sign up to set email alerts
|

The use of a responder analysis to identify differences in patient outcomes following a self-care intervention to improve cancer pain management

Abstract: Previously, we demonstrated, in a randomized clinical trial, the effectiveness of a psychoeducational intervention to decrease pain intensity scores and increase patients' knowledge of cancer pain management with a sample of oncology patients with pain from bone metastasis. In the present study, we evaluated for changes in mood states (measured using the Profile of Mood States), quality of life (QOL; measured using the Medical Outcomes Study Short Form-36 (SF-36)), and pain's level of interference with functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 42 publications
1
42
1
Order By: Relevance
“…These scores are similar to those reported in one study, 60 lower than scores reported in three studies of patients with advanced cancer, [61][62][63] and higher than scores reported in another study 64 of patients with advanced cancer. Reasons for these inconsistencies may include differences in studies' definition of advanced cancer, their inclusion and exclusion criteria, and timing of the assessments.…”
Section: Discussionsupporting
confidence: 88%
“…These scores are similar to those reported in one study, 60 lower than scores reported in three studies of patients with advanced cancer, [61][62][63] and higher than scores reported in another study 64 of patients with advanced cancer. Reasons for these inconsistencies may include differences in studies' definition of advanced cancer, their inclusion and exclusion criteria, and timing of the assessments.…”
Section: Discussionsupporting
confidence: 88%
“…This analysis put interpretations of localized brain function at risk. To move further afield, Tidwell, Dougherty, Chrabaszcz, Thomas, and Mendoza (2014) reviewed the measures used in brain-training studies (e.g., Jaeggi, Buschkuehl, Jonides, & Shah, 2011;Miaskowski et al, 2007). In one common analysis, participants whose performance was affected by training ("responders"), and those whose performance does not change ("nonresponders") are treated as separate groups.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…One successful approach to the statistical analysis of PROs which directly integrates clinical meaningfulness is to prespecify the clinically meaningful score change in the PRO measure, and plan to quantify the proportion of study participants who experience that change at a prespecified time point(s) of interest (i.e. responders) [22]. The approach for handling missing data should be specified for both missing questions within a scale and completely missing questionnaires, including at least two different sensitivity analyses involving missing data methods such as multiple imputation [1].…”
Section: Analysis Of Prosmentioning
confidence: 99%